Dynamics and Conflict Potential on Fish Resource Utilization in the Sawu Sea National Park: A Case Study in Rote Ndao Regency, East Nusa Tenggara - Jotham S R Ninef; Luky Adrianto; Zairion; Beatrix Maureen Rehatta (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2025)
The Sawu Sea National Park (SSNP) is a critical marine conservation area that supports the sustainability of fish resources and the livelihoods of coastal communities in Rote Ndao Regency. This study aims to analyze the dynamics of fish resource utilization in the Traditional Sustainable Fisheries (TSF) sub-zone, examine actor networks and catch distribution, and identify potential conflicts and strategic issues in small-scale fisheries management. A mixed-methods approach was applied, including a quantitative survey, in-depth interviews, field observations, and spatial analysis using GIS. The findings reveal the presence of external fishers utilizing modern fishing gear within the TSF sub-zone, leading to increased exploitation pressure and rising conflict potential. Declines in CPUE, fish size, and the disappearance of particular species are early signs of overfishing. Overlapping fishing grounds among fleets exacerbate social tensions and threaten ecological sustainability. Strategic recommendations include enhanced monitoring, evidence-based adaptive zoning, participatory conflict resolution, habitat restoration, and incentives for eco-friendly fisheries. This study underscores the importance of participatory and collaborative governance approaches to ensure the sustainability of fish resources in conservation areas.